Photoinduced hole hopping through tryptophans in proteins - Záliš, Stanislav; Heyda, Jan; Šebesta, Filip; Winkler, Jay R; Gray, Harry B; Vlček, Antonín (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Hole hopping through tryptophan/tyrosine chains enables rapid unidirectional charge transport over long distances. We have elucidated structural and dynamical factors controlling hopping speed and efficiency in two modified azurin constructs that include a rhenium(I) sensitizer, Re(His)(CO)3(dmp)+, and one or two tryptophans (W1, W2). Experimental kinetics investigations showed that the two closely spaced (3 to 4 Å) intervening tryptophans dramatically accelerated long-range electron transfer (ET) from CuI to the photoexcited sensitizer. In our theoretical work, we found that time-dependent density-functional theory (TDDFT) quantum mechanics/molecular mechanics/molecular dynamics (QM/MM/MD) trajectories of low-lying triplet excited states of ReI(His)(CO)3(dmp)+-W1(-W2) exhibited crossings between sensitizer-localized (*Re) and charge-separated [ReI(His)(CO)3(dmp•-)/(W1•+ or W2•+)] (CS1 or CS2) states. Our analysis revealed that the distances, angles, and mutual orientations of ET-active cofactors fluctuate in a relatively narrow range in which the cofactors are strongly coupled, enabling adiabatic ET. Water-dominated electrostatic field fluctuations bring *Re and CS1 states to a crossing where *Re(CO)3(dmp)+←W1 ET occurs, and CS1 becomes the lowest triplet state. ET is promoted by solvation dynamics around *Re(CO)3(dmp)+(W1); and CS1 is stabilized by Re(dmp•-)/W1•+ electron/hole interaction and enhanced W1•+ solvation. The second hop, W1•+←W2, is facilitated by water fluctuations near the W1/W2 unit, taking place when the electrostatic potential at W2 drops well below that at W1•+ Insufficient solvation and reorganization around W2 make W1•+←W2 ET endergonic, shifting the equilibrium toward W1•+ and decreasing the charge-separation yield. We suggest that multiscale TDDFT/MM/MD is a suitable technique to model the simultaneous evolution of photogenerated excited-state manifolds.
Keywords: Azurin; tryptofan; azurin; Electrons; elektrony; simulace molekulární dynamiky; fotochemie; voda; rhenium; Static Electricity; Molecular Dynamics Simulation; electron transfer; kvantová teorie; transport elektronů; molecular dynamics; Tryptophan; oxidace-redukce; Electron Transport; Pseudomonas aeruginosa; statická elektřina; Photochemistry; hole hopping; tryptophan; Rhenium; Quantum Theory; Oxidation-Reduction; Water